College majors and the knowledge content of jobs - James A. Freeman; Barry T. Hirsch (Institute for the Study of Labor (IZA), 2007)
College students select their majors for a variety of reasons, including expected returns in the labor market. This paper demonstrates an empirical method that links a census of U.S. degrees and fields of study with measures of the knowledge content of jobs. The study combines individual wage and employment data from the Current Population Survey (CPS) with ratings on 27 knowledge content areas from the Occupational Information Network (O*NET), thus providing measures of the economy-wide knowledge content of jobs. Fields of study and the corresponding BA degree data from the Digest of Education Statistics for 1976-77 through 2001-02 are linked to these 27 content areas. We find that the choice of college major is responsive to changes in the knowledge composition of jobs and, more problematically, the wage returns to types of knowledge. Women's degree responsiveness to knowledge content appears to be stronger than men's, but their response to wage returns is weak.
Keywords: 330; Studienfach; Berufswahl; Wissen; Bildungsertrag; USA